(3edLC GdbVGI YfO JYGQV GdHjfGJs - (3ZGfe Hf eMeO GdHZOGOj, GdMfaj ZjGK GdOjf, CHh eMeO,J (B1030 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHg fSJYjf SHMGf ef dG MLI Cbhi ef cdGeg hHYO ajbhd GdYHO GdabjQ Edi GdZfi CHh eMeO ZGfe Hf eMeO GdHZOGOi gPg QSGdI ai JYGQV GdHjfGJ cJH LeYJgG dHYV ENhGfi hbO SejJg edLC GdbVGI YfO JYGQV GdHjfGJ s
(3BNQgG (B:s
(3GdfgGjI hJcdehG ai GdeLJgO bGd HYVge ef SFd Yf YTQ eSGFd ajUjH ai GdKeGfjI hEf cGfJ GdeSCdI ai ZjQ XGgQ GdQhGjI hdjaJi HeG YfOg UhGH hGdMeO ddg Ydi GdJeGe hYdi QShdg CaVd GdUdGI hGdSdGe s
(3HgG fXGe GdJYbjHIs
(3cJHJ CSeGA GdCHhGH HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B307 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B38 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B812s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1816s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs